2023
DOI: 10.1136/bcr-2022-252468
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy after a recent SARS-CoV-2 infection

Abstract: SARS-CoV-2 infections can induce kidney injury and glomerulopathy, with the most common pathology findings being acute tubular injury and collapsing glomerulopathy.Here we describe a rare case of membranous nephropathy in a man in his late 70s presented with nephrotic syndrome and rapidly progressive kidney dysfunction 1 month after SARS-CoV-2 infection. Phospholipase A2 receptor antibodies were positive. He was treated with rituximab, with proteinuria control. We review the cases reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Viruses can trigger immune-mediated kidney disease flare-up, nephrotic syndrome, and acute rejection in transplant patients. Accordingly, recent studies have indicated that SARS-CoV-2 infection possibly causes similar consequences in children [17][18][19][20][21]. This situation is one of the important negativities caused by COVID-19, such as acute disease and post-COVID conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses can trigger immune-mediated kidney disease flare-up, nephrotic syndrome, and acute rejection in transplant patients. Accordingly, recent studies have indicated that SARS-CoV-2 infection possibly causes similar consequences in children [17][18][19][20][21]. This situation is one of the important negativities caused by COVID-19, such as acute disease and post-COVID conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 42 There are reports of MN cases that occurred in temporal relationship with COVID-19 (23 cases) but only 7 cases have clinical information available. 18 , 43 , 44 , 45 , 46 , 47 Pathophysiology of MN in COVID-19 remains unclear but may be related to immune dysregulation resulting in auto-antibodies production. 46 …”
Section: Kidney Pathology Potentially Related To Covid-19mentioning
confidence: 99%
“…There were 4 patients (66.7%) that received immunosuppression: one with tacrolimus, one with cyclophosphamide, one with methylprednisolone, and one with rituximab. 18 , 44 , 45 , 46 Two patients received conservative management. Two patients (40%) required dialysis and eventually died.…”
Section: Kidney Pathology Potentially Related To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is highly critical to investigate the relationship between COVID-19 and kidneyrelated diseases. Initial research focused on the correlation between COVID-19 and AKI; however, emerging studies have indicated the potential onset or recurrence of glomerular diseases following COVID-19, including collapsing glomerulopathy, IgA nephropathy, and membranous nephropathy (MN) (5)(6)(7)(8)(9)(10). MN is a prevalent and clinically signi cant glomerular disorder with complex pathogenesis; it involves the production of autoantibodies against podocyte antigens localized on the glomerular basement membrane (11).…”
Section: Introductionmentioning
confidence: 99%